Kemalangan di rumah di kalangan kanak-kanak yang mendaftar di Institut Pediatrik, Hospital Kuala Lumpur - Abu Yamin K.; Azizi A.; Che Hatikah C.H.; Maa T.W.; Mazilinda M.; Mohd Fadhly Y.; Premilla G.P.; Rafidah Hanim M. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1995)
The objective of this study was to investigate the incidence of home accidents among children. The term 'accident' in this study refered to cases involving falls, cuts, poisoning and burns. Studies on 38 patients admitted ti Pediatric Institute, Hospital Kuala Lumpur (IPHKL) from November 1993 - November 1994 was carried out in order to determine the risk factors associated with home accidents. The results showed that 32 of the cases (84.2%) were 6 years of age and below, and males made up 52.6% of the cases. As for ethnicity, the majority were Malays (63.2%) followed by Chinese and Indians (both 18.4%) of sample. The study also showed that the majority of accident occurred among children of non working mothers (52.6%). In addition 89.5% of cases were involved, those with fewer than 5 siblings. Cases where patients were not the only child in the family cinstituted 76.3%. In this study only one risk factor was recognised as being significant and that is child caring. Arrangement where children who were not taken care of by their own mothers risk of being involved in home accidents was three time higher compared to those who were.